The justice of Constantine : law, communication, and control - Dillon, John Noël (Law and society in the ancient world., 2012)
As the first Christian emperor of Rome, Constantine the Great has long interested those studying the establishment of Christianity. But Constantine is also notable for his ability to control a sprawling empire and effect major changes. The Justice of Constantine examines Constantine's judicial and administrative legislation and his efforts to maintain control over the imperial bureaucracy, to guarantee the working of Roman justice, and to keep the will of his subjects throughout the Roman Empire. John Dillon first analyzes the record of Constantine's legislation and its relationship to prior legislation. His initial chapters also serve as an introduction to Roman law and administration in later antiquity. Dillon then considers Constantine's public edicts and internal communications about access to law, trials and procedure, corruption, and punishment for administrative abuses. How imperial officials relied on correspondence with Constantine to resolve legal questions is also considered. A study of Constantine's expedited appellate system, to ensure provincial justice, concludes the book. Constantine's constitutions reveal much about the Theodosian Code and the laws included in it. Constantine consistently seeks direct sources of reliable information in order to enforce his will. In official correspondence, meanwhile, Constantine strives to maintain control over his officials through punishment; trusted agents; and the cultivation of accountability, rivalry, and suspicion among them.